Neurofeedback and Sport - Wilson, S. (Biofeedback, 2001)
While there is a quantity of research demonstrating the relationship between EEG and sport, there is little research on Neurofeedback in sport. The study by Landers Petruzzello, Salazar, Crews, Kubitz, Grannon, and Han (1991) illustrates how NF was provided to experienced athletes with documented changes in sport performance. The authors presented a framework showing how performance is developed in sport. A task analysis of the sport is the first requirement followed by `deliberate practice` of the appropriate skills. The training schedule then needs to be `periodized` and then `individualized`. With this information the neurotherapist can more reasonably select NF goals and protocols. Neurofeedback is proposed as being most viable for sport-specific attention regulation, imagery, motivation and `therapeutic` interventions. In addition to collaborative research, we recommend that neurotherapists can contribute to the knowledge in the field by adapting the single-subject case design to identify the individual zone of optimal functioning.